Sulfurized Carbon: A Class of Cathode Materials for High Performance Lithium/Sulfur Batteries - Zhang, Sheng S. (Frontiers in Energy Research, 2013)
Liquid electrolyte lithium/sulfur (Li/S) batteries cannot come into practical applications because of many problems such as low energy efficiency, short cycle life, and fast self-discharge. All these problems are related to the dissolution of lithium polysulfide, a series of sulfur reduction intermediates, in the liquid electrolyte, and resulting parasitic reactions with the Li anode. Covalently binding sulfur onto carbon surface is a solution to completely eliminate the dissolution of lithium polysulfide and make the Li/S battery viable for practical applications. This can be achieved by replacing elemental sulfur with sulfurized carbon as the cathode material. This article reviews the current efforts on this subject and discusses the syntheses, electrochemical properties, and prospects of the sulfurized carbon as a cathode material in the rechargeable Li/S batteries.